EFFECT OF DIFFERENT STORAGE CONDITIONS ON QUALITY OF PLUM (PRUNUS SELICINA LINDL.) PULP CV. SUTLEJ PURPLE - S. S. KUNDU; R. K. SHARMA; R. K. GOYAL; , S. SIDDIQUI; C. BISHNOI (The Bioscan, 2015)
Experiment was conducted to study the effect of different storage conditions on quality of pulp of plum. The pulp samples were pasteurized and stored at ambient, refrigerated (6±2°C) and frozen temperature (-10±5°C). The pulp was analyzed for quality parameters at 15 days of interval up to 4 month of storage. The maximum total soluble solids (11.39%) and acidity (1.79%) were found in the pulp stored at room temperature, while minimum was observed in pulp stored at frozen temperature (11.13% and 1.74% respectively). The maximum ascorbic acid (8.02 mg/100g) content was found in pulp stored at frozen temperature and it decreased progressively with the increase in storage period. The maximum total sugars (8.66%) were recorded in pulp stored at room temperature but no effect was recorded on reducing sugars. No significant changes in total and reducing sugars were observed up to 90 th day of storage; however, in later storage periods it increased significantly. There was no microbial infection and browning in the pulp and it remained suitable for further use even after 120 days of storage. The pulp stored at frozen temperature showed stability for physicochemical attributes in comparison to other treatments during 120 days of storage.